Effects of vertical shaft geometry on natural ventilation in urban road tunnel fires - Ji, Jie; Fan, Chuan Gang; Gao, Zi He; Sun, Jin Hua (Journal of Civil Engineering and Management, 2014)
A set of burning experiments were conducted to investigate the effect of vertical shaft geometry on natural ventilation in urban road tunnel fires. Results show that using vertical shafts to discharge smoke leads to a boundary layer separation near the right-angle connection of the shaft and the tunnel ceiling. In a low shaft, the turbulent-boundary-layer separation phenomenon causes relatively large-scale vortexes and restricts smoke from being exhausted, resulting in a negative effect on natural ventilation. Replacing the right-angle connection with the bevel-angle connection was proposed to split one separation point into two separation points, to attenuate the negative effect. The detailed characteristics of the separation phenomenon were analysed and the proposition was verified by Large Eddy Simulation. Results show that there are no relatively large-scale vortexes in shafts with bevel-angle connections, resulting in improved natural ventilation effectiveness. For lower shafts, the advantage of using the bevel-angle connection is more significant, and for shafts of the same height, the mass flow rate of smoke discharged by shafts with the bevel-angle connection increases up to 1.5 times of that by shafts with the right-angle connection. For relatively high shafts, it is about 1.2 times.